Hospital Performance Measurement Analysis: Case Study Using the Balanced Scorecard Method - Yulitasari, Yulitasari; Semiarty, Rima; Lestari, Yuniar (Newinera Publisher, 2025)
Performance measurement is an important factor for companies in assessing success. Company performance measurement usually only focuses on measuring financial perspectives. Ibnu Sina Islamic Hospital Payakumbuh still uses performance measurement in the financial aspect, not comprehensively and not from a non-financial perspective. to analyze the performance measurement of Ibnu Sina Islamic Hospital Payakumbuh in 2023 using the Balanced Scorecard (BSc) method. qualitative with a problem approach through descriptive analysis. The research was conducted at Ibnu Sina Islamic Hospital Payakumbuh. The research activities were carried out in February - September 2024. Selection of research informants using the purposive sampling method, namely the selection of informants who are considered to know the problem more broadly and deeply. The results of measuring performance indicators in each perspective, some have reached the target/standard and some have not. Of the 28 performance indicators measured, 13 indicators have reached the standard/target (46%), while the other 15 indicators (54%) have not reached the standard/target. The performance of the financial perspective on the economic ratio was not achieved. Customer perspective performance from average patient growth has decreased. Service quality is not achieved due to lack of commitment. Internal business process perspective performance BOR, ALOS and BTO are not achieved. Learning perspective performance and employee retention growth, employee training, employee productivity, information technology development have not been achieved. Suggestion: to hospital management, it is necessary to conduct socialization and commitment to all stakeholders regarding the vision, mission, goals and targets to be achieved as common goals and targets.